ANALISIS KRITIS MAKNA “AL-SYABAB” DAN “ISTITHA’AH” PADA HADITS ANJURAN MENIKAH - Mawardi Sufyan, Akhmad Farid (Universitas Islam Madura, 2017)
Marriage is a matter advocated by religion. This is because marriage is a encouraging behavior for the realization of Maqashid al-Shariah, precisely Hifdz al-Nasl (keeping the offspring). But the reality is there to be worse when it turns out the marriage ushers humans on conditions that are not better and even worse. The facts on the ground are that many young mothers die after childbirth due to maturation factors of the sexual organs and immature labor, and other social anomalies. Whereas the idealism of marriage is accompanying children and grandchildren to prosper. In psychology studies mentioned that marriages are built not on the basis of emotional maturity susceptible to problems. This fact provides a logical consequence, that the marriage proposal for every youth does not apply to everyone. Married advice is only for young people who have psychological maturity. This is called takhsish bi al-'aqli bi thariqi al-musnahadah. By using this takhsis analysis it can be taken to understand that the advisable youth (الشباب ) married on the content of the hadith is only specific to the adult youth of 25 years. The conclusions of this study are: 1) The meaning of